P069 Sleep Restriction Impairs Integration of Multiple Information Sources in Probabilistic Decision-Making. (9th November 2022) - Lim, J; Boardman, J; Anderson, C; Dickinson, D; Drummond, S
Abstract: Introduction: Sleep loss affects overall decision-making, but its effects on specific mechanisms of decision-making are less well-understood. Here, we examined the effects of sleep restriction (SR) on the ability to integrate multiple information sources on a probabilistic decision-making task. Methods: We recruited 41 healthy participants (n=41; age=27.9±6.0years, 20F), 27 of whom underwent well-rested ( WR: 4 nights of 9-hours time-in-bed) and SR (3 nights of 3-hours time-in-bed) conditions in counterbalanced order. On the last day of each lab stay, participants completed a probabilistic decision-making task twice – 2-hours after wake (AM) and 12-hours since habitual wake (PM). On each trial, participants were shown two boxes with different proportions of black/white balls. Eight balls were drawn randomly, with replacement, from an unknown box. Participants determined the selected box using easier-to-understand numerical odds and harder-to-understand draw outcome information. Mathematical modelling was used to infer weights placed on each source of information. Results: For AM and PM sessions, participants placed significantly greater weights on odds relative to draw information during WR (p<.001 for both). For AM trials, SR significantly reduced weights given to draw information (p=.041), and reduced weights given to odds at marginally significant levels (p=.062). For PM trials, SR reduced weights given to draw information at marginally significant levels (p=.059). Conclusion: While well-rested individuals generally rely more on easier-to-understand information, SR impairs decision-making by further reducing individuals' ability to consider more complex information. This has implications for high-risk professions where SR is common (e.g. doctors) and impaired decision-making may pose serious consequences.